2019
DOI: 10.1002/ps.5489
|View full text |Cite
|
Sign up to set email alerts
|

The impact of cover crops on the predatory mite Anystis baccarum (Acari, Anystidae) and the leafhopper pest Empoasca onukii (Hemiptera, Cicadellidae) in a tea plantation

Abstract: BACKGROUND Empoasca onukii, the tea green leafhopper, is a key pest of tea whose control often requires the extensive use of insecticides. As a predator of the tea green leafhopper, the mite Anystis baccarum is a potential biological control agent worldwide, though little is known about how intercropping cover crops can impact its suppressing effect on E. onukii. Therefore, we conducted a field experiment to investigate how the relationship of the abundance of the predatory mite and its leafhopper prey is infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 31 publications
1
26
0
Order By: Relevance
“…Hemiptera have caused heavy economic losses in many crops, including fruit, vegetables and cereal . However, little information is available about the function of opsin in Hemiptera, therefore more research is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Hemiptera have caused heavy economic losses in many crops, including fruit, vegetables and cereal . However, little information is available about the function of opsin in Hemiptera, therefore more research is imperative.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, weeded, bare ground rows (Bar) also showed significantly higher species richness than in the control. The underlying mechanisms of the two significant differences, however, are probably different; C. rotundifolia likely attracts beneficial insects by providing shelter or other resources (Chen et al , 2019a, b), whereas bare soil surfaces open up opportunities for ambush predators to easily find prey (Schmidt & Rypstra, 2010). Since these normally generalist species that are specifically adapted to disturbed habitats are more likely to stay in the adjacent field margins, their long-term value in tea canopies as biological control agents may be limited.…”
Section: Discussionmentioning
confidence: 99%
“…Existing evidence on efficacy of cover crops in enhancing beneficial species in tea plantations is mixed (Chen et al , 2019a, b). Song et al (2006) found that predatory Coleoptera abundance was significantly higher in tea interplanted with white clover ( Trifolium repens L., 1753) compared to tea monocultures, and this change led to better suppression of hemipteran pests.…”
Section: Introductionmentioning
confidence: 99%
“…However, these applications represent increased costs for tea growers and can have adverse effects on the environment and on natural enemy populations which can result in pest resurgence [ 1 , 11 ]. Alternatively, numerous other control agents and methods against this pest have been proposed, including biological control [ 12 ], physical control [ 13 ], and chemical intervention [ 14 , 15 , 16 ]. However, the management of this pest remains challenging.…”
Section: Introductionmentioning
confidence: 99%